Re-visiting catenary structures : Towards new spatial properties - Eslam Abdelkhalek Metwally Sayed Metwally; Khaled Mohamed Dewidar; Mohamed Medhat Dorra (Cairo : Eslam Abdelkhalek Metwally Sayed Metwally, 2021)
Nowadays due to the variety of materials in the construction market, new materials could be used in shell construction; such as resin with clear crystal effect, which can give a new spatial property to such structures. The research aim is to develop a prototype for a grid shell structure made of transparent polymer. Research objective was set to facilities the achievement of its aim, by firstly building a background about shells and form find a catenary grid. As, it will be the simplified example for shells in order to experiment new material and spatial property. Moreover, identifying the local materials to be used
Thesis (M.Sc.) - Cairo University - Faculty of Engineering - Department of Architectural Engineering
Issued also as CD
Keywords: Form Finding; Grid Shells; Shell Structures